A novel dual closed-loop control scheme based on repetitive control for grid-connected inverters with an LCL filter. (March 2018) - Gao, Yun-Guang; Jiang, Fa-Yang; Song, Jian-Cheng; Zheng, Li-Jun; Tian, Fei-Yan; Geng, Pu-Long
Abstract: Grid-connected inverters with LCL filters need high steady-state control accuracy, fast dynamic response performance, and strong robustness to guarantee the power quality. However, there are many problems in traditional control strategies that restrict improvements to control system performance, such as poor dynamic performance of traditional single-repetitive control, large ripples, low steady-state accuracy of inverter current feedback based repetitive dual-loop control or grid-current feedback based single-loop proportional-integral control. In this paper, a novel dual closed-loop repetitive control strategy based on grid current feedback is proposed for single-phase grid-connected inverters with LCL filters. The proportional-integral inner loop is stabilized by using an inherent one-beat delay achieved by digital controller. Based on the inner loop system, a detailed design scheme of a repetitive controller is presented, through which direct control of the grid current is realized, the reference is tracked perfectly to a zero phase shift, and high-attenuation gain is achieved in the high frequency range. In particular, the gird-voltage feed forward control and current reference feedforward control are adopted to suppress grid-voltage disturbance and increase dynamic tracking performance. Finally, the simulation and experimental results show that the proposed method has the advantages of high steady-state accuracy, fast dynamic response, and anti-disturbance ability. Highlights: The active damping method based on digital PI is proposed to realize the stability of the LCL filter. A novel dual closed-loop repetitive control strategy based on grid current feedback is proposed. A reference current feedforward link and grid-voltage feedforward link are designed to enhance the system dynamic response. Based on frequency characteristic analysis, the judging formula of stability and anti-disturbance performance is derived.